Triptolide inhibits the progression of Glioblastoma U251 cells via targeting PROX1 - Yuan, Chao; Liao, Yanli; Liao, Shengjie; Huang, Mi; Li, Duanzhuo; Wu, Weibin; Quan, Yi; Li, Liqiang; Yu, Xin; Si, Wenxia (Frontiers in Oncology, 2023)
Background: Glioblastoma multiforme (GBM) is the most lethal brain cancer in adults, characterized by rapid growth, extensive invasiveness, and poor prognosis, and there is still a lack of effective treatments. Here, we aimed to explore the role of triptolide (TPL), purified from Tripterygium wilfordii Hook F, on glioblastoma cell growth, apoptosis, proliferation, migration and invasion, as well as potential underlying mechanisms. Methods: The publicly available clinical data of brain Lower Grade Glioma (LGG) from The Cancer Genome Atlas (TCGA) had been screened to observe PROX1 expression. The Kaplan-Meier analysis was used to analyze the relationship between PROX1 expression and GBM prognosis. CCK8, cell cycle, EDU, apoptosis, wound healing, and transwell assays were performed to detect the effects of TPL on glioblastoma U251 cell viability, cell cycle, proliferation, apoptosis, migration and invasion, respectively. Further, a soft agar colony assay was used to calculate the growth of glioblastoma cells. The qRT-PCR and western blot were conducted to quantify PROX1 mRNA and protein levels. The transcriptional regulation of TPL was detected by Dual luciferase reporter assay. Results: We found that TPL inhibited glioblastoma cell viability, proliferation, cell cycle, migration and invasion, but enhanced apoptosis in a dose-dependent manner. The expression of cell cycle inhibitor, P21, and pro-apoptosis factor, Bax was increased, while invasion-related factors MMP2 and MMP9 were silenced after TPL treatments. Mechanistically, TPL showed transcriptional inhibition of PROX1 appearance. Moreover, ectopic expression of PROX1 partially rescued the effects of TPL on glioblastoma cell viability, proliferation, apoptosis, migration and invasion, and on the expression of cell function-related genes. Conclusion: This study verified that TPL inhibited the progression of glioblastoma cells by transcriptionally depressing the expression of PROX1.